2015
DOI: 10.1016/j.neo.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Derived Tumor Xenografts Are Susceptible to Formation of Human Lymphocytic Tumors

Abstract: Patient-derived xenograft (PDX) tumor models have emerged as a new approach to evaluate the effects of cancer drugs on patients’ personalized tumor grafts enabling to select the best treatment for the cancer patient and providing a new tool for oncology drug developers. Here, we report that human tumors engrafted in immunodeficient mice are susceptible to formation of B-and T-cell PDX tumors. We xenografted human primary and metastatic tumor samples into immunodeficient mice and found that a fraction of PDX tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 24 publications
6
85
1
Order By: Relevance
“…Recently, the PDX mouse model has been used to identify personalized therapy for cancer patients [44]. In our study, a subcutaneously transplanted tumor model of ICC and two PDX mouse models demonstrated the anti-tumor effects of RA190 in vivo.…”
Section: Discussionmentioning
confidence: 62%
“…Recently, the PDX mouse model has been used to identify personalized therapy for cancer patients [44]. In our study, a subcutaneously transplanted tumor model of ICC and two PDX mouse models demonstrated the anti-tumor effects of RA190 in vivo.…”
Section: Discussionmentioning
confidence: 62%
“…And DLBCL PDXs tend to form large metastases and grow faster than CRC PDXs which basically do not metastasize when grown subcutaneously in immunocompromised mice [9, 16]. As shown in Table 1, the days for growth tended to be shorter in DLBCL PDX than in CRC PDX.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, 2 out of 9 PDXs showed morphological characteristics of lymphoma (22.2%). Although the number of the reports on the lymphomagenesis in PDXs are still limited, other two reports present that the incidence of lymphomagenesis in the PDX transplanted with human CRC tissues was 3.3% (1/30) and 28.6% (2/7) [8, 9], suggesting that it is important to consider a possibilities of the lymphomagenesis when establishing PDX using the patient CRC tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Validation is required to confirm the PDX tumor is of the appropriate patient, and not of murine origin nor consisting primarily of Epstein-Barr virus (EBV) Human B lymphocytic cells as both are frequently observed in PDX model creation(9). Other “desirable” quality assurance methods vary with tumor types and can include histopathology, assessment of human cancer biomarkers by immunohistochemistry, in situ hybridization, and assessment of gene mutations and rearrangements, DNA methylation or gene expression profiling.…”
Section: The Pdx-minimal Information (Pdx-mi) Standardmentioning
confidence: 99%